Analisis Perbandingan Profitabilitas sebelum dan setelah Penerapan CSR Pada PTAngkasa Pura II Cabang Bandar Udara Soekarno Hatta Tangerang - Jonathan Lucky Sasmitha; Fasya Ridlwansyah (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2020)
This study was conducted to determine differences inprofitability before and after the implementation of Corporate Social Responsibility (CSR), as well as the implementation of CSR on profitability relationship in PT Angkasa Pura II Soekarno Hatta Airport in Tangerang. The data use disreported total assets and net income (loss) before applying and after the implementation of CSR, as well as therealization of the CSR budget period. Based on analysis of paired samples t test, the fact remains that there are significant differences on the profitability of PT Angkasa Pura II Soekarno Hatta Tangerang after applying CSR, but the differenceis negative because after application of the CSR, the average ROI decreased. Nevertheless, the correlation of the test results, it was found that the implementation of CSR has apositif connectionto profitabilitas be based on ROI.